Expression profile of the carbon reserve remobilization from the source to sink in rice in response to soil drying during grain filling. (1st April 2020) - Wang, Guanqun; Li, Haoxuan; Gong, Yulong; Yang, Jianchang; Yi, Yake; Zhang, Jianhua; Ye, Nenghui
Abstract: Moderate soil drying (MD) applied during the mid‐to‐late grain filling stages can promote carbon reserve remobilization in straws (sheaths and stems) and increase the grain weight. The coordination between starch‐to‐sucrose transition in straws and sucrose‐to‐starch conversion in inferior grains is essential for carbon reserve remobilization during grain filling. Herein, to reveal the regulating mechanism of carbon reserve remobilization from source to sink, RNA‐seq was utilized to analyze the dynamic transcript profile in source and sink of rice under MD treatment during grain filling. The expression of amylase genes and amylase activity was enhanced by MD treatment in straws, which is consistent with the increased amylase activity. In inferior grains, it was starch synthesis genes that were upregulated by MD treatment. Furthermore, an elevated ABA was found in both straws and inferior grains, which was caused by an increased expression of NCED1 and downregulation of ABA8OX2 by MD treatment, respectively. Additionally, the expression of MYB30, a transcription factor (TF) that negatively regulates beta‐amylase genes, was reduced in straws by MD, resulting in an increased amylase activity. In contrast, an increased expression of NAC activated the expressions of starch synthesis gene in inferior grains under MD. Therefore, it is MYB30 and NAC that cooperates in source and sink, respectively, to promote carbon reserve remobilization in response to MD. Taken together, genes involved in carbon flow from source to sink are different between rice straws and inferior grains. Abstract : We reported the transcriptome profile of source and investigated the relationship of source to sink in carbon reserve remobilization during grain filling under MD. The cooperation of gene expression between source and sink plays a key role during grain filling, including the downregulated MYB30 negatively regulates beta‐amylase genes at the transcriptional level in source under MD during grain filling and upregulated NAC activated expression of WAXY genes in sink during grain filling under MD.